L’enfant et la ville : deux exemples de bandes dessinées tout public (1992-2020) - Martine Motard-Noar (Strenae)
This article is a study of two French contemporary comic book series for young people aged 9 and over: Titeuf (1992-2021) by Zep et Lou ! (2004-2020) by Julien Neel. The article is an analysis of the complexity of the representation of children in the city in the two series. While depicted in traditional ways, streets and buildings come into play on the page to support the narration in these comics. The city is also a complex and potentially problematic space for the child and pre-adolescent characters, even when the story has a humoristic tone and expands its horizon to fire escape balconies and rooftops, as it does in Lou !. This genre, with its general target audience, is a fundamentally urban genre because all its main characters live in the city and place themselves resolutely in this context. Nevertheless, the series Lou ! and Titeuf eventually point to the value of what is outside the city: nature, seen as important initiatory training, a step in the process of evolution for pre-adolescent characters.